In silico designing of siRNA targeting PB 1 gene of Influenza A virus and in vitro validation - Bhawana Jain, Amita Jain, Om Prakash, Ajay Kr Singh, Tanushree Dangi, Mastan Singh, Kaleshwar P Singh (Journal of Applied Pharmaceutical Science, 2014)
Genomic variability makes Influenza A virus (IAV) ‘the least susceptible’ to existing vaccines or anti-influenza drugs. siRNA targeting viral gene silents the gene by cleaving mRNA. Present study aimed to develop siRNA targeting polymerase basic 1 (PB1) gene and to validate its efficiency in vitro. siRNA was designed rationally, targeting the most conserved region of PB1 gene of IAV strains. Total 147 strains worldwide and 42 Indian strains, when aligned, showed seven sets of conserved regions (> 30 bp stretch and < 5% mismatches). To choose the most efficient siRNA, three levels screening method was developed. Finally one pair of siRNA was chosen due to its unique position in conserved region. siRNA efficacy was confirmed in vitro on Madin Darby Canine Kidney (MDCK) cell line propagating two clinical isolates i.e. Influenza A/H3N2 [A/India/LKO864/ 2011(H3N2)] and Influenza A/pandemicH1N1 [A/India/LKO2151/2012(H1N1)]. The longest ORF was targeted by the selected siRNA, which showed 57 % inhibition in replication of Influenza A/pdmH1N1 and 60.6 % inhibition in replication of Influenza A/H3N2 at 72 hpi and 48 hpi respectively on MDCK cell line. This study shows that siRNA targeting PB1 may be moderately effective in controlling IAV replication so can be used as anti-IAV therapeutic agent.
Keywords: Influenza A virus, siRNA designing, multiple sequence alignment, MDCK cell line, in vitro validation, PB1 gene.